(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
A woman is who can be a leader, a teacher, a mother, or a well-wisher. A woman can do anything if she decides to do. Women are doing excellent in many areas like and achieving their goals in competitive world. They are not in any boundaries but crossing the boundaries and reaching on top. The chief aim of the research paper is to find out the demographic profile of women leader at different zone in higher educational sector. Women’s are achieving their goals in many fields like aerospace, doctors, teaching, kitchen, police, politics and many more. Women leaders are at every place and at everywhere. Women leaders are in different place, zone, city, village everywhere in Gujarat zone. As a result, the maximum qualification of women leaders is doctorate degree. We can also say that the maximum number of women leaders are from west zone of Gujarat state.